Stilbenes: Chemistry and Pharmacological properties - Roat, Chetana; Saraf, Meenu (Journal of Applied Pharmaceutical Research, 2015)
Medicinal plants are the most important source of life saving drugs for the majority of the worldÃ¢â¬â¢s population. The compounds which synthesized in the plant from the secondary metabolisms are called secondary metabolites; exhibit a wide array of biological and pharmacological properties. Stilbenes a small class of polyphenols, have recently gained the focus of a number of studies in medicine, chemistry as well as have emerged as promising molecules that potentially affect human health. Stilbenes are relatively simple compounds synthesized by plants and deriving from the phenyalanine/polymalonate route, the last and key enzyme of this pathway being stilbene synthase. Here, we review the biological significance of stilbenes in plants together with their biosynthesis pathway, its chemistry and its pharmacological significances.